Development of an Information System for Sales of Building Materials in a Building Store Using Model View Controller (MVC) - Nur Hidayati (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
One area that has an important role in the business world is sales. There are different types of goods and services offered to the wider community and can be used to meet their needs. One example is the material of the building that is used as materials to build a house, building, school and other buildings. The building's material items are sold in the Building Store. However, most of the processing of data on the sale of building materials in the Building Store is still done conventionally, thus causing problems. Like, there were errors in data recording, data searches that took a long time, and the making of inaccurate sales reports. If this is allowed to happen, then the place of the venture could suffer a lot of losses and not be able to take the right steps to resolve the existing problem. Therefore, the place of the venture requires the construction of a system, especially for the sales information system. With the development of the system, it is hoped that we will solve existing problems and be able to monitor the performance of the system and evaluate it well. And in the development of the system, it has to be supported with the use of the right method, where one of the methods that can be used is MVC (Model View Cotroller). Using this MVC, we can see the data structure used, the view and also the list of programs for the creation of the program application. The sales program applications generated from the development of this system, of course, are very much expected to help improve the existing system and improve the service and generate accurate data